Pengembangan Modul Fluida Statis Berbasis Problem Based Learning untuk Meningkatkan Keterampilan Proses Sains dan Sikap Ilmiah Siswa Kelas XI MAN 2 Lubuklinggau - Rahayu Premesti; Sulistiyono Sulistiyono (Journal on Education, 2024)
The study aims to (1) produce a static fluid module based on Problem Based Learning that is feasible to improve the science process skills and scientific attitudes of grade XI students of MAN 2 Lubuklinggau (2) determine the improvement of students‘ science process skills after using the static fluid module based on Problem Based Learning and (3) determine the improvement of students’ scientific attitudes after using the static fluid module based on Problem Based Learning. The research method used in the research is Reseach and Development using the ADDIE development model there are five stages, namely: Analysis, Design, Development, Implement, Evaluate. The results showed that (1) The problem-based learning static fluid module is feasible to use to improve the science process skills and scientific attitudes of grade XI students of MAN 2 Lubuklinggau with the results of material expert validation of 60, media expert 70, linguist 45 with very good category (2) The increase in science process skills of 94.81 with a high category and (3) The increase in scientific attitudes after using the Problem Based Learning-based static fluid module of 87.26 with a high category